2010
DOI: 10.1071/ch09420
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Selective Cytotoxicity of Organometallic Cp*RuII O-Alkyl-N-phenylcarbamate Sandwich Complexes

Abstract: Tetraphenylborate salts of the η 6 -arene Cp * Ru II O-alkyl-N-phenyl carbamate organometallic sandwich complexes, [Cp * Ru(PhNHCO 2 R)]BPh 4 for R = Me (1), Et (2), and n-Pr (3), have been prepared by a facile one-pot reaction between ruthenium trichloride, pentamethylcyclopentadiene, and phenylisocyanate in refluxing alcohol solutions, and have been characterized by Fourier-transform IR and NMR spectroscopy, electrospray mass spectrometry, and single-crystal X-ray structure determinations. In vitro cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…This effect is due to the electronwithdrawing nature of the [(h 5 -Cp*)Ru] þ fragment. In this way the [(h 5 -Cp*)Ru] þ group has been shown previously to catalyze the conversion of aromatic carboxylic acids in ethanol to ethyl esters [8,32], benzaldehydes in methanol to benzaldehyde dimethyl acetals [27], aromatic isocyanates to carbamates [20], and aromatic chlorides to fluorides [33]. During the present study the carbonyl carbon electrophile of complex (1) was found to be a versatile starting material for a range of nucleophilic substitution reactions involving nucleophiles such as alcohols, primary and secondary amines and aromatic sulfonamides.…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
“…This effect is due to the electronwithdrawing nature of the [(h 5 -Cp*)Ru] þ fragment. In this way the [(h 5 -Cp*)Ru] þ group has been shown previously to catalyze the conversion of aromatic carboxylic acids in ethanol to ethyl esters [8,32], benzaldehydes in methanol to benzaldehyde dimethyl acetals [27], aromatic isocyanates to carbamates [20], and aromatic chlorides to fluorides [33]. During the present study the carbonyl carbon electrophile of complex (1) was found to be a versatile starting material for a range of nucleophilic substitution reactions involving nucleophiles such as alcohols, primary and secondary amines and aromatic sulfonamides.…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
“…The promising antitumor effects displayed by these cationic organoruthenium molecules prompted us to synthesize and biologically evaluate structurally diverse libraries of ruthenium(II)-based full-sandwich complexes (Figure 1; in which R represents a series of substituted functional groups including carboxylic acids, acid fluorides, esters, thioesters, ketones, alcohols, carbamates, amides, sulphonamides, and glycoconjugates. [9] The results of these studies demonstrated the cationic organoruthenium complexes to possess potent and selective antiproliferative activity towards a range of cancerous cell lines in vitro, including human skin carcinoma (MM96L) and two individual phenotypes of breast cancer (MCF7 and MDA-MB-231), with the degree of growth inhibition dependent on the size and lipophilicity of the arene ligand. [9] Of particular interest, however, was the relative inactivity of the neutral ruthenocenyl complexes when compared to their corresponding cationic derivatives.…”
Section: -Arene)a C H T U N G T R E N N U N G (Y à Z)l]mentioning
confidence: 98%
“…[9] The results of these studies demonstrated the cationic organoruthenium complexes to possess potent and selective antiproliferative activity towards a range of cancerous cell lines in vitro, including human skin carcinoma (MM96L) and two individual phenotypes of breast cancer (MCF7 and MDA-MB-231), with the degree of growth inhibition dependent on the size and lipophilicity of the arene ligand. [9] Of particular interest, however, was the relative inactivity of the neutral ruthenocenyl complexes when compared to their corresponding cationic derivatives. These mono-, 1,1'-di-, and pentasubstituted ruthenocenyl molecules were on average over two orders of magnitude less active than the respective cationic complexes, highlighting a relationship between positive charge and cytotoxic activity.…”
Section: -Arene)a C H T U N G T R E N N U N G (Y à Z)l]mentioning
confidence: 98%
See 2 more Smart Citations